Legal Analysis of WTO Dispute Settlement Mechanism Application in US 19% Tariff Case Against Indonesia for Trade Justice - Muhammad Wendra; Andri Sutrisno (Mimbar Keadilan, 2026)
This research stems from the reciprocal and protectionist policy of increased import tariffs by the United States, which disrupts free trade that has been functioning properly and creates injustice in international trade. Especially toward Indonesia, which was also affected by this policy, where the 19% reciprocal agreement with the United States still resulted in violations of international law, as determined by the WTO. Regarding this, this study aims to provide a legal analysis of the importance of the potential application of WTO dispute resolution to the United States' 19% tariff policy in its reciprocal agreement with Indonesia in order to achieve justice in the international trading system. This research uses a normative legal research method by examining international regulations (protocols) implemented by the WTO to ensure dispute resolution and the conduct of international trade processes. The results of this study indicate that the 19% import tariff policy by the United States thru its reciprocal agreement with Indonesia still violates import tariffs, the principle of good faith, and international trade monopolies. Therefore, Indonesia has the potential to resolve the dispute at the WTO by challenging the 19% tariff policy. This research recommends that a country, particularly Indonesia in this case, pursue formal dispute resolution within the WTO, including retaliation, as well as diplomatic approaches to find common ground (a win-win solution) for both parties.